Associations between Depressive Symptomatology and Neurocognitive Impairment in HIV/AIDS. (May 2018) - Tymchuk, Sarah; Gomez, Daniela; Koenig, Noshin; Gill, M. John; Fujiwara, Esther; Power, Christopher
Objective: Mood disorders and neurocognitive impairments are debilitating conditions among patients with HIV/AIDS. How these comorbidities interact and their relationships to systemic factors remain uncertain. Herein, we investigated factors contributing to depressive symptomatology (DS) in a prospective cohort of patients with HIV/AIDS in active care that included neuropsychological assessment. Methods: Among patients with HIV/AIDS receiving combination antiretroviral therapy (cART) and ongoing clinical assessments including measures of sleep, health-related quality of life (HQoL), neuropsychological testing, and mood evaluation (Patient Health Questionnaire–9 [PHQ-9]) were performed. Univariate and multivariate analyses were applied to the data. Results: In 265 persons, 3 categories of DS were established: minimal (PHQ-9: 0-4; n = 146), mild (PHQ-9: 5-9; n = 62), and moderate to severe (PHQ-9: 10+; n = 57). Low education, unemployment, diabetes, reduced adherence to treatment, HIV-associated neurocognitive disorders (HAND), low health-related quality of life (HQoL), reduced sleep times, and domestic violence were associated with higher PHQ-9 scores. Motor impairment was also associated with more severe DS. In a multinomial logistic regression model, only poor HQoL and shorter sleep duration were predictive of moderate to severe depression. In this multivariate model, the diagnosis of HAND and neuropsychological performance (NPz) were not predictive of DS. Conclusions: Symptoms of depression are common (45%) in patients with HIV/AIDS and represent a substantial comorbidity associated with multiple risk factors. Our results suggest that past or present immunosuppression and HAND are not linked to DS. In contrast, sleep quality and HQoL are important variables to consider in screening for mood disturbances among patients with HIV/AIDS and distinguishing them from neurocognitive impairments.